PE Teaching Activities in Colleges and Universities Based on Decision Tree - Chen, Jian (International Journal of Emerging Technologies in Learning (iJET), 2018)
To improve the efficiency of student's sports performance management and the quality of physical education teaching, the overall structure of the sports performance management system based on decision tree was designed, and a systematic database design plan was proposed. Then, ASP.NET technology was used. Combined with SQL Server database, on the Visual Studio platform, the implementation process of sports test type, test items and score management was given through the flow chart of the program. Moreover, the decision tree of the relationship between the sports performance and the students' employment was generated. It was proved that the efficiency of the sports teachers' entry and statistical results were improved through the construction of this system. it is concluded that the sports performance and the sports teaching based on rule are better developed through the system of data mining.